Competition and succession in pastures (CABI, 2001)
This multi-author book describes how competition between plant species and succession in plant ecosystems operate in natural and sown pastures. It discusses how competition affects botanical structure, productivity and persistence, and is itself regulated by biological, environmental and management factors. It includes chapters on grass-legume competition, diversity in humid temperate pastures, formulation of seed mixtures, effects of large herbivores on competition and succession in savanna rangelands, the interaction of competition and management in native pastures, effects of climatic change, and the measurement of competition and competition effects in pastures.